Legacies and Relationships: Diverse Social Networks and BRCA1/2 Risk Management Decisions and Actions. (February 2019) - Ersig, Anne L.; Werner-Lin, Allison; Hoskins, Lindsey; Young, Jennifer; Loud, Jennifer T.; Peters, June; Greene, Mark H.
In families with hereditary breast/ovarian cancer, complex disease histories challenge established patterns of family communication and influence decision-making for clinical surveillance, genetic testing, and risk management. An interdisciplinary team examined longitudinal interview data from women with identified BRCA1/2 mutations to assess interactions within family and social networks about risk information communication and management. We used interpretive description to identify motivation, content, and derived benefit of these interactions. Participants discussed risk information and management strategies with biological and nonbiological network members for multiple purposes: discharging responsibility for risk information dissemination, protecting important relationships, and navigating decision trajectories. Evolving interactions with loved ones balanced long-standing family communication patterns with differing personal preferences for privacy or open sharing, whereas interactions with nonbiological network members expanded participants' range of choices for sources of risk management information. Ongoing assessment of social networks may help support engagement with risk management by aligning with patient social needs.